META ANALYSIS ON CROPPING PATTERN INFLUENCING MARKETING SYSTEM - R. RAJESHKANNAN (International Journal of Pharma and Bio Sciences, 2016)
Agriculture plays a vital role in improving Indian economy. Food, fiber, biofuel and medicinal products obtained from it which is essential for sustainability of human life. The crops are cultivated in a state based on its demand and availability of natural resources. In order to market the cultivated crop in an efficient manner, the merchant needs information such as productivity of that crop in particular locations and its demand in the market. The agricultural information system is available to assist the merchant in an efficient crop marketing. Thereby it provides information such as if the productivity of the crop increases in the state, the cost of the crop in that state will decrease and the cost of buying the same crop in a state where the yield is less will increase. Therefore, based on the analysis of this Information System the merchant can decide which crop has to buy from which state and to sell in which state and hereby giving him the maximum profit out of the transaction.